Patterns of drug usage in a representative sample of students and teachers at University of Costa Rica in 2017 - Arias Zapata, Andrés (2018)
Objective: analyze patterns of drug usage by students and teachers at University of Costa Rica in 2017, applying a digital survey, which was sent to a representative sample of this population through email and social networks. Results: It was found that the higher proportion of the sample buy their drugs community pharmacies and practice self-medication in a seldom manner; almost always follow the indications given by health professionals; storage those drugs in the bedroom, in a box or drawer; don’t use to check expiration dates frequently and dispose non-usable drugs in common garbage recipients; they ignore the non-usable drugs collection campaigns that take place in the country, but they will be willing to attend lectures about rational drug use. Conclusions: The analyzed consumer profile shows serious issues in some aspects of drugs’ procurement, usage, storage and disposal, which could be solved with a better divulgation of collection campaigns as well as learning strategies developed by University of Costa Rica and also at community pharmacies